Role of Matrix Metalloproteinase-2 in Eosinophil-Mediated Airway Remodeling - Kuwabara, Yu; Kobayashi, Tetsu; D'Alessandro-Gabazza, Corina N.; Toda, Masaaki; Yasuma, Taro; Nishihama, Kota; Takeshita, Atsuro; Fujimoto, Hajime; Nagao, Mizuho; Fujisawa, Takao; Gabazza, Esteban C. (Frontiers in Immunology, 2018)
Airway remodeling is responsible for the progressive decline of lung function in bronchial asthma. Matrix metalloproteinase-2 and fibroblast-to-myofibroblast transition are involved in tissue remodeling. Here we evaluated whether eosinophils play a role in fibroblasts-to-myofibroblasts transition and in the expression of matrix metalloproteinase-2. We co-cultured human eosinophils with human fetal lung fibroblast-1 cells, assessed the expression of remodeling-associated molecules by immunoassays and polymerase-chain reaction, and eosinophils-mediated migration of human fetal lung fibroblast-1 cells using a Boyden chamber. To clarify the participation of matrix metalloproteinase-2 in airway remodeling we administered bone marrow-derived eosinophils by intra-tracheal route to transgenic mice overexpressing the human matrix metalloproteinase-2. The expression of α-smooth muscle actin significantly increased in human fetal lung fibroblast-1 cells co-cultured with human eosinophils compared to controls. There was enhanced expression of matrix metalloproteinase-2 during fibroblast-to-myofibroblast transition. An inhibitor of matrix metalloproteinases blocked eosinophils-associated fibroblast-to-myofibroblast transition and increased migration of fibroblasts. The human matrix metalloproteinase-2 transgenic mice receiving adoptive transfer of mouse eosinophils exhibited increased inflammation and advanced airway remodeling compared to wild type mice. This study demonstrated that eosinophils induce fibroblast-to-myofibroblast transition, secretion of matrix metalloproteinase-2, accelerated migration of fibroblasts and promote matrix metalloproteinase-2-related airway remodeling. These findings provide a novel mechanistic pathway for eosinophil-associated airway remodeling in bronchial asthma.